2017
DOI: 10.3354/aei00241
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on growth, protein turnover and energy budget of green and white color morphs of sea cucumber Apostichopus japonicus (Selenka)

Abstract: A 98 d experiment was conducted to compare the growth performance, protein turnover and energy budget between green and white color morphs of the sea cucumber Apostichopus japonicus. During the experiment, sea cucumbers were fed a single natural diet of Sargassum thunbergii and a premixed artificial diet. Results showed that there was no significant interaction of diet, species or experimental time on growth performance and feed utilization of A. japonicus. Specific growth rate (SGR) of green sea cucumber was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Mean DOC concentration in D8 was significantly higher than the others (Zhang et al, 2014;Zhang et al, 2022), which might influence the surrounding water environment counteracting self-growth, and resulting in the lowest feeding carbon content and the lowest metabolism carbon (Hou et al, 2017). Nitrogen is well known as a major element in protein, the content of which directly represents the utilization efficiency of protein in organisms (Xia et al, 2017b;Xia et al, 2017a). In the present study, it has been found that the percent of G N /C N and G N / A N were negatively correlated with stocking densities, while a positive correlation was detected in the percent of U N /A N and F N /C N with stocking densities.…”
Section: Discussionsupporting
confidence: 53%
“…Mean DOC concentration in D8 was significantly higher than the others (Zhang et al, 2014;Zhang et al, 2022), which might influence the surrounding water environment counteracting self-growth, and resulting in the lowest feeding carbon content and the lowest metabolism carbon (Hou et al, 2017). Nitrogen is well known as a major element in protein, the content of which directly represents the utilization efficiency of protein in organisms (Xia et al, 2017b;Xia et al, 2017a). In the present study, it has been found that the percent of G N /C N and G N / A N were negatively correlated with stocking densities, while a positive correlation was detected in the percent of U N /A N and F N /C N with stocking densities.…”
Section: Discussionsupporting
confidence: 53%
“…Sea cucumber Apostichopus japonicus (Selenka) is an important mariculture species in China. The farming scale has been rapidly expanded in the last decades due to the increasing market demand (Xia et al, 2017b). The production of this species has reached 220,000 t in 2017, with 110% increase compared to 2009 (MOAC, 2010; MOAC, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…During the feeding trial, A. japonicus grew from 9.99 g to 14.67–21.60 g with an acceptable SGR (0.71–1.11%/d), as compared to the growth data from other studies [ 17 , 48 50 ]. These positive growth responses fit quadratic regression models and thus confirm that phosphorus deficiency or excess could hinder the growth of A. japonicus as reported in a previous study on tiger shrimp [ 26 ].…”
Section: Discussionmentioning
confidence: 72%